The value of the Historical Archives: beyond History. A citizenship’s vision - Cagigal Montalbán, Ekain (Revista General de Información y Documentación, 2022)
Historical archives represent valuable cultural spaces for the citizens’ personal enrichment. Accordingly, this paper aims at articulating and describing the multiple dimensions of the value resulting from the approach of the users to the historical collections, undoubtedly distinguishing a citizen profile from professional scholars. Thus, at least, four attributes are proposed leading to meaningfulness in the interaction between users and archival resources, namely literary value, ludic value, educational value, and identity value. The main novelty lies on contributing to a joint overview between institutions and citizenship, provided this time from the counterpart of the archives, i.e., a citizenship’s vision.
Keywords: Historical archives; Citizenship; Value or the archives; Cultural function; History